2009
DOI: 10.1121/1.3058635
|View full text |Cite
|
Sign up to set email alerts
|

Children’s annoyance reactions to aircraft and road traffic noise

Abstract: Since annoyance reactions of children to environmental noise have rarely been investigated, no source specific exposure-response relations are available. The aim of this paper is to investigate children's reactions to aircraft and road traffic noise and to derive exposure-response relations. To this end, children's annoyance reactions to aircraft and road traffic noise in both the home and the school setting were investigated using the data gathered in a cross-sectional multicenter study, carried out among 284… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 23 publications
3
35
0
1
Order By: Relevance
“…In the cross-sectional multi-country RANCH study, a curvilinear exposure response relationship was demonstrated between exposure to aircraft noise at school and severe annoyance in children adjusting for confounding factors [18]. The percentage of severely annoyed children increased from about 5.1 % at 50 dB to 12.1 % at 60 dB.…”
Section: Annoyancementioning
confidence: 98%
“…In the cross-sectional multi-country RANCH study, a curvilinear exposure response relationship was demonstrated between exposure to aircraft noise at school and severe annoyance in children adjusting for confounding factors [18]. The percentage of severely annoyed children increased from about 5.1 % at 50 dB to 12.1 % at 60 dB.…”
Section: Annoyancementioning
confidence: 98%
“…Furthermore, recent studies have revealed that children indeed are capable of distinguishing annoyance and perceived health as measured by means of self-reported symptoms. 8,35 …”
Section: G Measurement Of Annoyance and Healthmentioning
confidence: 98%
“…Psychometric results justify the use of a simple sum-score of these items. 8 When participants answered that they suffered at least once a week from headache, vomiting, stomachache, difficulty falling asleep, or were woken at night or felt sleepy during the day, this was scored as a "symptom." Subsequently, for every child the total number of "symptoms" was counted.…”
Section: Perceived Healthmentioning
confidence: 99%
See 2 more Smart Citations